Components of impactful dementia training for general hospital staff: a collective case study. (3rd March 2020) - Surr, Claire A.; Sass, Cara; Burnley, Natasha; Drury, Michelle; Smith, Sarah J.; Parveen, Sahdia; Burden, Sarah; Oyebode, Jan
Abstract: Background and objectives: People with dementia occupy around one quarter of general hospital beds, with concerns consistently raised about care quality. Improving workforce knowledge, skills and attitudes is a mechanism for addressing this. However little is known about effective ways of training healthcare staff about dementia. This study aimed to understand models of dementia training most likely to lead to improved practice and better care experiences for people with dementia, and to understand barriers and facilitators to implementation. Method: A collective case study was conducted in three National Health Service Acute Hospital Trusts in England. Multiple data sources were used including interviews with training leads/facilitators, ward managers and staff who had attended training; satisfaction surveys with patients with dementia and/or carers; and observations of care using Dementia Care Mapping. Results: Interactive face-to-face training designed for general hospital staff was valued. Simulation and experiential learning methods were felt to be beneficial by some staff and stressful and distressing by others. Skilled delivery by an experienced and enthusiastic facilitator was identified as important. Staff identified learning and practice changes made following their training. However, observations revealed not all staff had the knowledge, attitudes and skills needed to deliver good care. Patient and carer satisfaction with care was mixed. A major barrier to training implementation was lack of resources. Supportive managers, organisational culture and strong leadership were key facilitators. Conclusion: Dementia training can lead to improved care practices. There are a range of key barriers and facilitators to implementation that must be considered.